Analysis of passively-damped coupled shear walls using continuum-based models. (1st October 2017) - Moghadasi Faridani, Hadi; Capsoni, Antonio
Highlights: Continuum-based models are used to analyze coupled shear walls with passive dampers. Distributed shear damping is employed to model velocity-dependent dampers. Two controlling parameters are defined to measure stiffness and supplementary damping. Global bending effect can be important in passively-damped coupled shear walls. Damping optimization issues can be simply studied using proposed continuum-based models. Abstract: This study assesses coupled shear walls (CSWs) equipped with passive damping systems using the damped continuum models developed as Coupled-Two-Beams (CTB). CTB models consisting of various distributed-parameter damping mechanisms are established. Numerical solutions for the dynamic analysis of these continuum systems are developed using a simple Finite Element (FE) model. It is illustrated how passive damping systems, viscous dampers and viscoelastic dampers, with various installation arrangements can be modeled with the use of the equivalent shear damping in a CTB system. Based on the dynamic analysis, the accuracy of damped CTBs with respect to different damping cases are verified. Two controlling parameters are introduced to evaluate the effect of both stiffness and supplementary damping on dynamical responses. The parametric study of passively-damped wall systems subjected to seismic loading is performed by emphasizing the effect of global bending and controlling parameters. Based on the important responses obtained from the dynamic analyses, optimal features of distributed damping such as damping length and its value are investigated with regard to the damping controlling parameter. This work shows that the developed CTB systems with the shear damping model are suitable tools for the dynamic analysis and the preliminary design of CSWs equipped with velocity-dependent dampers.